Healthcare expenditures in rural and urban areas: explanations for the differences - Haller, Lance (Kansas State University, 2008)
This paper on the urban and rural healthcare expenditures gap examines common explanations for why the gap exists. The rural communities have consistently had lower healthcare expenditures than that of the urban communities. Over the years the gap has decreased, but not by a significant amount. According to a 2003 U.S. Census, for people over 65 the gap was nearly double. For people under 65 the gap was significantly smaller, but still exists. There are many factors that lead to the healthcare expenditure gap and there are also many possible solutions to manipulate these factors. This paper will separate these factors, explain them and look at the pros and cons of some possible solutions.
Keywords: Healthcare; Expenditures; Rural; Urban; Economics, General (0501)